Governance Dimension and Sustainable Development in Nigeria’s Telecommunication Sector: Social, Environmental, and Economic Decarbonization Pathways. - Lateef Abdulsalam (PT Keberlanjutan Strategis Indonesia, 2026)
In response to growing global demands for sustainable development, this study explores how governance structures within the telecommunication sector influence organizational commitment to sustainability. Specifically, it examines the relationship between sustainable development efforts and three core governance dimensions: social governance, environmental governance, and economic decarbonization. Grounded in institutional theory, the study hypothesizes that stronger governance across these domains is positively associated with higher levels of sustainability commitment. Using Pearson correlation analysis on a sample of 95 telecommunication entities, the results reveal statistically significant positive correlations across all dimensions. The strongest association was observed between sustainable development and social governance (r = 0.472, p < 0.001), followed by economic decarbonization (r = 0.437, p < 0.001), and environmental governance (r = 0.373, p < 0.001). These findings suggest that while each governance domain contributes meaningfully to sustainability efforts, none alone serves as a dominant predictor. The moderate strength of these correlations underscores the importance of a holistic, integrated governance approach that simultaneously addresses social equity, environmental stewardship, and economic transformation. This research offers actionable insights for policymakers, corporate leaders, and sustainability practitioners aiming to align governance strategies with sustainable development goals in the telecommunication industry.